Asymmetric decentralisation arrangements in the implementation of regional autonomy in Indonesia - Allo, Hanfree Bunga'; Ilmar, Aminuddin; Ilmar, Aminuddin; Razak, Abdul (Edelweiss Applied Science and Technology, 2025)
This research aims: 1) to find, review, and analyze the importance of asymmetrical decentralization in the implementation of regional autonomy; 2) to find, review, and analyze the form of asymmetrical decentralization arrangements in the implementation of regional autonomy in Indonesia; and 3) to find the ideal concept of asymmetrical decentralization arrangements in the implementation of regional autonomy in Indonesia. The type of research is normative legal research, strengthened by a statutory approach, conceptual approach, and analytical approach. The legal materials used are primary legal materials and secondary legal materials. Primary and secondary legal materials that have been systematically synchronized are then further reviewed based on existing laws and legal theories so that research findings and conclusions are obtained. The results of the study show that: 1) Asymmetrical decentralization is important in the implementation of regional autonomy in Indonesia because it respects the privileges and specificities of the regions as stipulated in Articles 18A and 18B of the 1945 Constitution, and to prevent regional disintegration. 2) The form of asymmetrical decentralization regulation in Indonesia is in the form of law. This arrangement not only distinguishes it from symmetrical regions but also from asymmetrical regions. Each asymmetrical region has a specialty or specificity that distinguishes it from other asymmetrical regions. This arrangement aims to maintain national unity and encourage the development of regions that require special attention. 3) The ideal concept of asymmetrical decentralization regulation takes two forms: first, creating standard criteria for asymmetrical decentralization in the Local Government Law, and second, establishing regional diversity based on the pattern of Central and Regional relations, cultural characteristics, diversity management, improving development inequality, and overcoming geographical and infrastructure challenges to support sustainable development.